2009
DOI: 10.2220/biomedres.30.337
|View full text |Cite
|
Sign up to set email alerts
|

Age-related changes in contraction and relaxation of rat diaphragm

Abstract: Age-related changes of physiological and biochemical properties were examined in the diaphragm muscle, which has particularly high activation compared to that of other skeletal muscles. The diaphragm from 10-week-, 50-week-and 100-week-old male Wistar rats were used to measure in vitro isometric contractile properties, sarcoplasmic reticulum (SR) Ca 2+ -ATPase activity, and myosin heavy chain (MHC) isoform composition. Although there were no significant differences in specific twitch tension of the diaphragm a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 21 publications
1
13
1
Order By: Relevance
“…For example, work from our lab in Fischer 344 rats showed an ~20% reduction in DIAm specific force in old (24 months of age; 50% survival) compared to young (6 months of age; 100% survival) animals (Gosselin et al, 1994). Subsequent work in Fischer 344 (Criswell et al, 1997; Powers et al, 1996; Smith et al, 2002) Fischer 344 × Brown Norway (Criswell et al, 2003) and Wistar (Imagita et al, 2009) rats confirmed an aging-related reduction in DIAm specific force. An aging-related reduction in DIAm specific force has also been reported in golden hamsters (Zhang and Kelsen, 1990).…”
Section: Muscle Fiber Type and Motor Unit Classificationmentioning
confidence: 86%
“…For example, work from our lab in Fischer 344 rats showed an ~20% reduction in DIAm specific force in old (24 months of age; 50% survival) compared to young (6 months of age; 100% survival) animals (Gosselin et al, 1994). Subsequent work in Fischer 344 (Criswell et al, 1997; Powers et al, 1996; Smith et al, 2002) Fischer 344 × Brown Norway (Criswell et al, 2003) and Wistar (Imagita et al, 2009) rats confirmed an aging-related reduction in DIAm specific force. An aging-related reduction in DIAm specific force has also been reported in golden hamsters (Zhang and Kelsen, 1990).…”
Section: Muscle Fiber Type and Motor Unit Classificationmentioning
confidence: 86%
“…The weak VT of C57BL/6J mice might reflect age-related alteration of respiratory effectors. Lung parenchyma and diaphragm contractile properties degrade with age in rodents, but during the senescent period (28,29), not as early as P240. The weak VT of C57BL/6J mice more likely reflects altered breathing regulations that impair correct adjustments of the central respiratory drive to physiological needs.…”
Section: Differences In Breathing Regulations: Possible Role Of 5-htmentioning
confidence: 99%
“…Importantly, mutations increasing life span are known to slow the progression of age-related muscle atrophy in worms (Kashyap et al 2011). Additionally, in mammals, age-related changes in skeletal muscle have been shown to affect physiological functions of distal organ systems other than skeletal muscle itself such as cardiovascular oxygenation and nerve conduction (Imagita et al 2009). …”
Section: Resultsmentioning
confidence: 99%